Theological Independence of Hadith Scholars and the Chronological Problems of Asy'ariyah-Maturidiyah: A Critical Analysis of Usamah Al-Azhari's Thought - Zumrotus Sholikatun Nurjanah; Alfoun Fajar Mubarak; Mohamad Farid Zaini (Universitas Islam Negeri Imam Bonjol Padang, 2026)
Usamah Al-Azhari's claim that the Hadith scholars follow the Ash'ariyah and Maturidiyah ‎creeds in the book Aqidah Al-Muhadditsin Wa Washilatuhum Bi Al-Tashawwuf has sparked ‎academic controversy because it ignores significant chronological and methodological gaps. ‎This study aims to test the validity of this claim by critically analyzing the theological ‎independence of the Hadith scholars. Using a qualitative approach that integrates ‎Krippendorff's content analysis and historical theology, this study evaluates the text of ‎Usamah's claim. It compares it with classical documents from the Hadith scholars, the ‎Ash'ariyah, and the Maturidiyah traditions. The research findings indicate that the Hadith ‎scholars possess an epistemological independence that cannot be reduced to the Ash'ariyah ‎or Maturidiyah framework. The chronological gap-where the Ash'ariyah and Maturidiyah ‎emerged in the 3rd century AH, long after the initial generation of Hadith scholars-proves a ‎historical anachronism in Usamah's mapping. Furthermore, despite both using the tafwidh ‎method, the Hadith scholars apply it with a textual-traditionalist approach that is ‎fundamentally different from the rationalistic Ash'ariyah ta'wil method and the rationalist-‎systematic Maturidiyah approach. The internal dialectics within the Hadith scholars' ‎tradition-such as Al-Ghazali's critique of textual codification and Ibn Khuzaymah's ta'wil ‎practices-further strengthen their methodological autonomy. This research contributes to ‎the reconstruction of Sunni theological historiography by affirming the position of the ‎Hadith scholars as an independent tradition, not merely followers of a posteriori theological ‎school.‎